Identification and Validation of a Novel Major Quantitative Trait Locus for Plant Height in Common Wheat (Triticum aestivum L.) - Wang, Zhiqiang; Hu, Haiyan; Jiang, Xiaojun; Tao, Yang; Lin, Yu; Wu, Fangkun; Hou, Shuai; Liu, Shihang; Li, Caixia; Chen, Guangdeng; Liu, Yaxi (Frontiers in Genetics, 2020)
Plant height (PH) plays a pivotal role in plant morphological architecture and is associated with yield potential in wheat. For the quantitative trait locus (QTL) analysis, a recombinant inbred line population was developed between varieties differing significantly in PH. Two major QTL were identified on chromosomes 4B (QPh.sicau-4B) and 6D (QPh.sicau-6D) in multiple environments, which were then validated in two different backgrounds by using closely linked markers. QPh.sicau-4B explained 10.1%–21.3% of the phenotypic variance, and the location corresponded to the dwarfing gene Rht-B1. QPh.sicau-6D might be a novel QTL for PH, explaining 6.6%–13.6% of the phenotypic variance and affecting spike length, thousand-kernel weight, and spikelet compactness. Three genes associated with plant growth and development were identified in the physical interval of QPh.sicau-6D. Collectively, we identified a novel stable and major PH QTL, QPh.sicau-6D, which could aid in the development of closely linked markers for marker-assisted breeding and cloning genes underlying this QTL.